التعليل في القرآن الكريم -سورة التوبة أنموذجا- - صولي, شوشة (University of Eloued جامعة الجزائر, 2020)
" هذه المذكرة عنوانها "" التعليل بين علم الكلام وعلم أصول الفقه""، دراسة تحليلية مقارنة، وإشكاليتها الرئيسة التي حررت المذكرة بغرض الإجابة عنها هي: ""ما حقيقة الاختلاف في إثبات العلّة ونفيها بين هذين العلميْن؟ وهل العلة المبحوثة في علم الكلام هي نفسها المبحوثة في علم أصول الفقه؟"". وقد جاء البحث في أربعة مباحث، خصص التمهيدي لضبط بعض المصطلحات، أمّا المبحث الأول فقد تناول مسألة التعليل في علم الكلام حيث ذكرت فيه المذاهب في ذلك، أما المبحث الثاني فقد تناول مسألة التعليل عند الأصوليين فذكرنا فيه المذاهب بأدلتها، أما المبحث الثالث فقد كان للمقارنة بين التعليلين في كلا العلميْن. ومن النتائج الرئيسة التي خرجنا بها في هذه المذكرة أن العلة المنفية في علم الكلام ليست هي المثبتة في علم أصول الفقه من قبل المتكلمين وبالتالي فلا يوجد تناقض. ومن أهم التوصيات التي نأمل بأن تؤخذ بعين الاعتبار هو إعادة احياء روح علم الكلام بين طلبة العلوم الشرعية وخاصة تخصص أصول الفقه فإنّ سبر غوره متوقف على تحصيل علوم الآلة والله أعلم. ""The summary of this thesis is entitled ""explanation between doctrine and the fundamentals of Fiqh"", a comparative analytical study, and its main forms, which edited the note for the purpose of answering it, are: ""What is the fact that the evidence and denial of the cause between these two sciences? Is the same cause as that of the doctrine?"" he said. The research came in four discussions, which were preliminary to some terms, and the first discussed the issue of explanation in the doctrine, in which doctrines were mentioned, while the second discussed the issue of explanation in fundamentalists, in which doctrines warned them to be exchanged. The third research was to compare the two explanations in bothsciences. One of the main findings of this thesis is that the doctrine is not established in the fundamentals of fiqh by speakers and therefore there is no contradiction. One of the most important recommendations that we hope to take into consideration is the revival of the spirit of the doctrine among the students of the legitimate sciences, especially the specialization of the fundamentals of fiqh, the lessons of his incompetence depend on the achievement of the sciences of the machine and God knows. "
مذكرة ماستر تخصص لغة ودراسات قرانية
Keywords: "التعليل" "علم الكلام" " أصول الفقه"; Reasoning_ ilamic belief_osolfekh